2003
DOI: 10.1111/j.1349-7006.2003.tb01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the coxsackievirus and adenovirus receptor in musculoskeletal tumors and mesenchymal tissues: efficacy of adenoviral gene therapy for osteosarcoma

Abstract: Recombinant adenovirus is used as a competent vector in a wide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
1
28
0
Order By: Relevance
“…This is consistent with the findings of Kawashima et al, who demonstrated expression of coxsackie-adenovirus receptor (CAR), which is crucial for efficient viral entry into cells, was high in musculoskeletal tumor cell lines and tissue samples. 46 All sarcoma cell lines exhibited a dosedependent decrease in cell viability when treated with Adwtp53 but not with Ad-mutp53. These results indicate that it is the gene product of Ad-wtp53 rather than the viral vector itself that is cytotoxic.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the findings of Kawashima et al, who demonstrated expression of coxsackie-adenovirus receptor (CAR), which is crucial for efficient viral entry into cells, was high in musculoskeletal tumor cell lines and tissue samples. 46 All sarcoma cell lines exhibited a dosedependent decrease in cell viability when treated with Adwtp53 but not with Ad-mutp53. These results indicate that it is the gene product of Ad-wtp53 rather than the viral vector itself that is cytotoxic.…”
Section: Discussionmentioning
confidence: 93%
“…This could be attributed to lower efficiency of infection from low expression of the CAR receptor. 46 Figure 1b shows the morphologic changes that occur when the sarcoma cell lines are treated with Ad-wtp53. All four cells lines showed evidence of lower cell density, lifting of cells off plate and membrane blebbing, an indication of apoptosis.…”
Section: Effect Of Ad-wtp53 On In Vitro Cell Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong correlation between the expression of CAR on the cell surface and the level of transgene expression in photochemically treated cells was observed, suggesting that the absolute level of virus binding to the cell surface determines the level of transduction in photochemically treated cells, as reported by other groups for conventional adenoviral infection. [18][19][20] Blocking CAR with recombinant Ad5 fiber-knob resulted in a complete inhibition of gene expression, both in conventionally infected and in photochemically treated cells. These results strengthen the assumption that attachment to the cell surface is a key event for PCI-mediated transduction and suggest further that nonreceptor-mediated uptake pathways are not involved in the photochemical transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Using the RmcB anti-CAR monoclonal antibody, 13 we found that the cell lines used in this study expressed different levels of CAR ( Table 1) Fig 1b), as previously reported by other groups. [18][19][20] The relationship between the expression of CAR and the percentage of b-galactosidasepositive cells in photochemically treated cells showed an even better linear correlation (P ¼ .002 , Fig 1b), suggesting that virus binding to the cell surface is of fundamental importance also for photochemical transduction.…”
Section: Influence Of Car On Photochemical Transductionmentioning
confidence: 99%